SARANA DAN PRASARANA DI PERPUSTAKAAN INSTITUT AGAMA ISLAM NEGERI PONTIANAK - Sabarina, Sabarina; Amir, Amriani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study aims to find out the facilities and infrastructure needed and what deficiencies are in the Institute's library. Pontianak State Islamic Religion and to know what will be added facilities and infrastructure in the Pontianak State Islamic Institute library. In this study the author uses the method used is descriptive method with qualitative research forms and data collection techniques conducted by researchers using observations directly to the field, interviews with the library head, management and secretaries of the Pontianak State Islamic Institute library and documentation when the research was conducted. From the results of research carried out the facilities and infrastructure of the Pontianak State Islamic Institute Library are sufficient and have used the National Standard of College Library but it still has shortcomings and there are some facilities that need to be added in the Pontianak State Islamic Institute Library. Keywords: Library Facilities and Infrastructure